Cross‐section positioning based on a dynamic MLS tunnel monitoring system. (9th August 2019) - Du, Liming; Zhong, Ruofei; Sun, Haili; Liu, Yujiao; Wu, Qiong
Abstract: The number of tunnels is increasing sharply, especially in China, due to the development of urban rail transit networks. It is thus crucial to study rapid structural deformation detection methods for tunnels in operation. A dynamic tunnel monitoring system can directly obtain cross sections. However, using only odometers to locate the cross sections along the track of a tunnel results in insufficient accuracy. Furthermore, the measured cross sections are all in local coordinate systems, providing no indication of curved tunnels and restricting 3D display capabilities. This paper focuses on a relative positioning method based on mobile laser scanning to improve the accuracy, together with a unified positioning method to relate the measured cross sections in a single system. The accuracy and applicability of the proposed methods are verified by experiments which demonstrate that the solutions can fully meet accuracy requirements and 3D display purposes. Abstract : It is crucial to study rapid detection methods for structural deformation in the increasing number of urban rail tunnels. Using only odometers to locate the cross sections using a dynamic tunnel monitoring system results in insufficient accuracy with the cross sections all in local coordinate systems, providing no indication of curved tunnels and restricting 3D display capabilities. This paper focuses on a relative positioning method based on mobile laser scanning to improve the accuracy, together with a unified positioning method for the measured cross sections. Résumé: Le nombre de tunnels ne cesse d'augmenter, notamment en Chine, en raison du développement des réseaux de transport ferroviaire urbain. Il est alors crucial d'étudier des méthodes de détection rapide de déformation structurale pour les tunnels en fonctionnement. Un système dynamique de surveillance de tunnel fournit directement des profils en travers. Cependant, l'utilisation des seuls odomètres pour localiser les profils le long du tunnel conduit à une précision insuffisante. De plus, les profils mesurés sont toujours dans des systèmes de coordonnées locales ce qui restreint les possibilités de représentation 3D. Cet article présente une méthode de positionnement relatif utilisant le balayage laser mobile pour améliorer la précision, ainsi qu'une méthode de positionnement unifiée por les profils mesurés. La précision et l'applicabilité des méthodes proposées sont évaluées par des expériences qui montrent que ces solutions répondent aux exigences de précision et aux besoins de représentation 3D. Zusammenfassung: Die Zahl von Tunnelbauwerken nimmt durch die Entwicklung von urbanen Schieneninfrastrukturnetwerken rapide zu. Dies gilt speziell auch für China. Hierbei ist es entscheidend, Methoden zu studieren, die eine schnelle Entdeckung struktureller Deformationen für Tunnel im Betrieb erlauben. Ein dynamisches Tunnelüberwachungssystem kann direkt Querprofile erfassen. Dadurch dass die Querprofile aber nur durch Odometer in Längsrichtung lokalisiert werden, ist die Genauigkeit unzureichend. Jedes Querprofil ist in einem lokalen Koordinatensystem erfasst, so dass keine Angaben über gekrümmte Tunnel erhalten werden und die 3D Visualisierungsmöglichkeiten eingeschränkt sind. Dieser Beitrag stellt eine realative Positionierungsmethode, basierend auf mobilem Laserscanning vor, um die Genauigkeit der Positionierung zu steigern und alle Querprofile in einem einheitlichen System zu erfassen. Die Genauigkeit und Anwendbarkeit der vorgeschlagenenen Methode werden durch Experimente verifiziert, die zeigen, dass die erzielten Ergebnisse die Genauigkeits‐ und die 3D Visualisierungsanforderungen erfüllen. Resumen: El número de túneles está aumentando considerablemente, especialmente en China, debido al desarrollo de las redes de transporte ferroviario urbano. Por lo tanto, es crucial estudiar métodos de detección rápida de deformación estructural de túneles en servicio. Un sistema dinámico de monitoreo de túneles puede obtener directamente secciones transversales. Sin embargo, usando solo odómetros para posicionar las secciones transversales a lo largo de un túnel no se obtiene suficiente precisión. Además, las secciones transversales medidas están todas en sistemas de coordenadas locales, lo que no proporciona ninguna indicación de túneles curvos y reduce las capacidades de visualización en 3D. Este documento se centra en un método de posicionamiento relativo basado en un sistema láser móvil para mejorar la precisión, junto con un método de posicionamiento unificado de las secciones transversales medidas. La precisión y la aplicabilidad de los métodos propuestos se han verificado mediante experimentos demostrando que las soluciones pueden cumplir los requisitos de precisión y los propósitos de visualización en 3D. 摘要: 随着城市轨道交通技术的快速发展, 隧道数量逐年递增。研究运营期隧道结构变形的快速检测方法至关重要。动态无控制隧道监测系统能够直接获取与隧道处处正交的横断面, 但是该系统中仅利用里程计进行隧道沿轨方向的断面定位, 精度不足;此外, 系统实测的断面数据均处于局部坐标系下, 使得隧道整体不具备线型, 限制了隧道的三维显示。为此, 本文基于该系统研究了隧道横断面的相对定位精度提升方法和统一定位方法, 并通过实验对方法进行精度和适用性的验证。结果表明该定位方法完全能够满足运营阶段隧道检测和三维显示的需求。